MPOWER: The Impact of a Purpose Program on Adolescents’ Intrinsic and Extrinsic Motivations - Sepulveda, Jonathan A.; Lincoln, Brenna; Liang, Belle; Klein, Timothy; White, Allison E.; Hill, Nancy; Perella, John (Frontiers in Psychology, 2021)
Purpose has been defined as an active engagement toward goals that are meaningful to the self (i.e., personal meaningfulness) and contribute to the world beyond the self (BTS). These BTS contributions may reflect the intention to meet a wide range of needs from family financial needs to more macro-level concerns, including social injustices. This study investigates the efficacy of a school-based program called MPOWER expressly designed by the authors to cultivate the BTS aspect of purpose. Previous research suggests that the BTS aspect of purpose has beneficial effects on school engagement, goal-setting abilities and orientations, and ultimately school performance. Ninety-four students participated in this study that utilized a randomized, pretest-posttest between-subjects design to evaluate MPOWER (52 in MPOWER and 42 in the control group). The ANCOVA results indicated a significant increase in the BTS aspect of purpose among program participants, compared to controls. Moreover, participants had higher posttest levels of general self-efficacy and grade point averages, and decreased performance-approach (e.g., playing to be the best, comparing self to others) and performance-avoidance (e.g., avoiding risks of failure, fear of social consequences) goal orientations. Findings can be used to design programs that aim to cultivate students’ intentions to contribute to the world beyond themselves, as well as associated personal benefits (i.e., goal orientations, self-efficacy, academic performance).